Non-invasive management of fused upper incisors - Samimi, Pouran (Medknow Publications & Media Pvt Ltd, 2012)
The union of two different dental sprouts which can happen in any phase of dental development is commonly called fusion. This developmental anomaly may cause clinical problems including esthetic impairment, which are mainly treated by endodontic and surgical treatments. There are a few reports of conservative not invasive treatment of fused incisors teeth through restorative or prosthetic techniques. They are rarely reported in mandibular posterior teeth. This paper presents an unusual case of fusion of 7 and 8, and also 9 and 10 teeth which was treated with a nonendodontic and nonsurgical conservative approach. Patient was a healthy18-year-old female with chief complaint of bad-looking teeth that in intraoral examination revealed the fusion of 7 and 8, and also 9 and 10 teeth. The space between the mesial of the 6 and 11 teeth was reconstructed. Diastema between the fused teeth was closed. A new lateral tooth was replaced between the fused teeth (7 and 8) and 6 tooth with direct fiber-reinforced composite. The space between the fused teeth (9 and 10) and also tooth 11 was partially closed. Gingival papillas were reconstructed using pink composite. The mandibular anterior missing teeth were replaced with rochett bridge. At the end of treatment the esthetic of the patient was improved. As the treatment was not invasive, major complications are not expected; however, there is potential for eventual long-term periodontal problems due to poor oral hygiene. Debonding of the rochett bridge may happen as well.